Evaluating retinal and choroidal perfusion changes after isometric and dynamic activity using optical coherence tomography angiography - Brinkmann, Max Philipp; Kibele, Nikolas Xavier; Prasuhn, Michelle; Kakkassery, Vinodh; Toro, Mario Damiano; Ranjbar, Mahdy; Grisanti, Salvatore; Becker, Matthias D.; Rommel, Felix (Diagnostics, 2021)
Optical coherence tomography angiography (OCTA) is a non-invasive tool for imaging and quantifying the retinal and choroidal perfusion state in vivo. This study aimed to evaluate the acute effects of isometric and dynamic exercise on retinal and choroidal sublayer perfusion using OCTA. A pilot study was conducted on young, healthy participants, each of whom performed a specific isometric exercise on the first day and a dynamic exercise the day after. At baseline and immediately after the exercise, heart rate (HR), mean arterial pressure (MAP), superficial capillary plexus perfusion (SCPP), deep capillary plexus perfusion (DCPP), choriocapillaris perfusion (CCP), Sattlers’s layer perfusion (SLP), and Haller’s layer perfusion (HLP) were recorded. A total of 34 eyes of 34 subjects with a mean age of 32.35 ± 7.87 years were included. HR as well as MAP increased significantly after both types of exercise. Both SCPP and DCPP did not show any significant alteration due to isometric or dynamic exercise. After performing dynamic exercise, CCP, SLP, as well as HLP significantly increased. Changes in MAP correlated significantly with changes in HLP after the dynamic activity. OCTA-based analysis in healthy adults following physical activity demonstrated a constant retinal perfusion, supporting the theory of autoregulatory mechanisms. Dynamic exercise, as opposed to isometric activity, significantly changed choroidal perfusion. OCTA imaging may represent a novel and sensitive tool to expand the diagnostic spectrum in the field of sports medicine.
Gesehen am 28.06.2021